Immunosensor for Detection of the Textile Dye Disperse Orange 1 Based on Non-conventional Competitive Assay - Venturini Uliana, Carolina [UNESP]; Yamanaka, Hideko [UNESP] (Wiley, 2019)
Textile dyes appear as an important class of compounds that has become a matter of public concern and a serious challenge for scientists and environmentalists due to their large-scale production and extensive application. In this work, a non-conventional competitive-type amperometric immunosensor was successfully developed for detection of the textile dye Disperse Orange 1 (DO1). The DO1 was magnetically captured and separated from the sample solution using magnetic particles (MP) functionalized with the antibody anti-DO1 and with HRP and gold electrodes were modified with the conjugate DO1-BSA. Molecules of DO1 immobilized on the electrode surface and DO1 captured by MP compete for antibody binding sites. As a result, the amperometric signal decreases with increasing target DO1 concentration at the capture step, because this decreases, the attachment between the HRP coated MP and the electrode. This strategy allowed us to determine DO1 at the low detection limit of 0.87 ng mL−1 with great specificity. Also, there were good recoveries for detection of the textile dye in river water samples without the need of sample pre-treatment. The competitive amperometric immunosensor shows applicability for the determination of small molecules that cannot be determined by conventional competitive or sandwich immunosensors.
Keywords: Competitive immunosensor; Magnetic particle; Small molecule; Textile dye